Resolving cryptic diversity in the Chromis viridis species complex (Pomacentridae): a multilocus phylogenetic and morphometric reassessment of species boundaries - M. U. Rekha; Teena Jayakumar T. K.; Abhilash C. P.; Ahamed Rasheeq A.; Saikrishnan K. R.; Vallarasu R.; Gladston Y.; Kajal Chakraborty; Ajithkumar T. T. (Frontiers in Marine Science, 2026)
The blue-green damselfish, Chromis viridis (Cuvier, 1830), is widely distributed across Indo-Pacific coral reefs and is among the most heavily traded marine ornamental fishes. Recent molecular studies have suggested the presence of cryptic diversity within the C. viridis complex, but species boundaries remain unresolved. Multilocus phylogenetic analyses incorporating three mitochondrial markers—cytochrome c oxidase subunit I (COI), cytochrome b (cytb), and the mitochondrial control region (D-loop)—and two nuclear markers, recombination-activating gene 1 (RAG1) and recombination-activating gene 2 (RAG2), were performed to assess lineage diversification within the Chromis viridis species complex. Specimens collected from the Lakshadweep Archipelago and the Gulf of Mannar, India, formed a distinct and well-supported lineage that was clearly separated from C. viridis sensu stricto and other congeners in phylogenetic reconstructions and genetic distance analyses. Multiple species-delimitation approaches consistently supported the recognition of this lineage as an independently evolving taxon, and morphometric analyses revealed corresponding differences in body proportions and meristic characters. Based on the concordance of molecular and morphological evidence, a new species, Chromis veneta sp. nov., is herein described from the Indian Ocean. The new species differs from C. viridis in having a relatively elongate body, narrower caudal peduncle, distinctive body pigmentation, yellowish to orangish distal fin margins, and a deeply forked caudal fin with elongate lobe tips. Additional diagnostic features include differences in dentition, gill-raker counts and sagittal otolith morphology. The discovery of C. veneta sp. nov. highlights underestimated diversity within the C. viridis complex and underscores the importance of integrative taxonomy in revealing cryptic reef-fish diversity.

Unveiling Growth Patterns and Condition Status of 25 Flatfish Species (Order: Pleuronectiformes) from the Southern Coast of Tamil Nadu, India: Evidence from Length–Weight Relationships - R. G. Sasikumar; P. Jawahar; N. Jayakumar; G. Arul Oli; T. Ravikumar; M. Sharumathi; J. Joyson Paul; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Length–Weight Relationships and Condition Factor of Fourteen Clupeiform Fishes from the Gulf of Mannar, Southeast Coast of India - M. Armaan Arnaa; N. Jayakumar; R. Durairaja; M. Kalaiarasan; K. Karuppasamy; C. Abishek; M. Sharumathi; J. Joyson Paul; R. G. Sasikumar (Thalassas: An International Journal of Marine Sciences, 2026)

Monsoon-driven seasonal variability in sediment texture of embayed beaches along the central west coast of India - Puneet Kumar Mishra; Mani Murali R; Deepika Dwivedi; SK Ariful Hossain; Santhosh Kumar S; Jayakumar Seelam; Shincy Francis; Richa Rai (Regional Studies in Marine Science, 2026)

Influence of carrier gas on the performance of humidification dehumidification desalination systems - J.S. Jayakumar; Raj Ranjitha; R. Ajith Kumar (Desalination, 2026)

Evaluating Climatic Trends through Mann-Kendall and Sen Slope Analysis of CMIP6 Model Downscaled Future Projections - Ankit Balvanshi; Jayakumar K.V.; V. R. Desai (Water Resources Management, 2026)

Deciphering Environmental Drivers on Plankton Dynamics in Punnakayal–Pazhayakayal Estuarine Complex, Southern Coast of India - Kamei Ringjonmeilu; N. Jayakumar; R. Durairaja; V. Rani; T. Ravikumar; R. Saravanan; C. Sudhan; Adyasha Sahu; J. Joyson Paul; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

Reproductive Biology and Population Dynamics of Bigeye Scad (Selar crumenophthalmus) in the Gulf of Mannar, India: Implications for Management - J. Joyson Paul; R. Durairaja; N. Jayakumar; M. Sharumathi; R. G. Sasikumar; K. Karuppasamy; Sanjay Chandravanshi; R. Tamilselvan (Thalassas: An International Journal of Marine Sciences, 2026)

Reproductive Traits and Population Characteristics of Atule mate (Cuvier, 1833) From the Gulf of Mannar: Implications for Minimum Legal Size - J. Joyson Paul; R. Durairaja; N. Jayakumar; M. Sharumathi; K. Karuppasamy; Percy Paulin J; S. Pearlin Arul Granap; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

Comparative Assessment of Length-Weight Relationship and Relative Condition Factor of 25 Grouper Species along the Southern Coast of Tamil Nadu, India - J. Joyson Paul; R. Durairaja; N. Jayakumar; N. Daniel; T. Ravikumar; M. Sharumathi; R. G. Sasikumar; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Optimizing the rice yield under future climate: joint insights for India and Sri Lanka - Ankit Balvanshi; Rashmi Patil; Harikumar Mohanan; Hari Lal Tiwari; K. V. Jayakumar; Venkappayya R. Desai (Regional Environmental Change, 2026)

Reproductive biology and population dynamics of the five-lined snapper Lutjanus quinquelineatus (Bloch, 1790) from the Gulf of Mannar: implications for establishing minimum legal-size limits - M. Sharumathi; N. Jayakumar; R. Durairaja; J. Joyson Paul; R. G. Sasikumar; K. Karuppasamy; S. Parkavi; S. Pearlin Arul Granap (Environmental Biology of Fishes, 2026)

Development of a novel Moving Bed Biofilm Reactor (MBBR) for treatment of wastewaters by improving the hydrodynamics - Himanshu Tiwari; Elsa Sony; Rahul Jayakumar; Sivaraman Savithri; Girish R. Pophali (Journal of Water Process Engineering, 2026)

Assessing the Demographic Characteristics and Exploitation Status of the Torpedo Scad, Megalaspis Cordyla (Linnaeus, 1758) Along the Gulf of Mannar Coast - J. Joyson Paul; R. Durairaja; N. Jayakumar; M. Sharumathi; R. G. Sasikumar; K. Karuppasamy; Adyasha Sahu (Thalassas: An International Journal of Marine Sciences, 2025)

Demographic Characteristics and Exploitation Status of the Blue Swimming Crab Portunus pelagicus (Linnaeus, 1758) Along the Palk Bay Coast, Southeast India - Pearlin Arul Granap S.; Durairaja R.; Jayakumar N.; Ranjith L.; Sudhan C.; Karuppasamy K.; Kalaiarasan M.; J. Joyson Paul; Nandhakumar M. (Thalassas: An International Journal of Marine Sciences, 2025)

Aquaculture of Asian seabass (Lates calcarifer) in India: A comparative economic analysis across production systems and regions - Geetha R.; Abhinaya D.; Naffees Gowsar S. R.; Ravisankar T.; Kailasam M.; Jayakumar R.; Subburaj R.; Shinoj P.; Rajni Jain; Lal K. K.; Patil P. K. (Aquaculture International, 2025)

Length–Weight Relationship and Relative Condition Factor of 20 Carangid Fish Species from the Gulf of Mannar, Southeast Coast of India - J Joyson Paul; R Durairaja; N Jayakumar; K V. Venkataramani; Thangaraji Ravikumar; M Sharumathi; Kishore Kumar; Sanjay Chandravanshi; Adyasha Sahu; C Sudhan (Thalassas: An International Journal of Marine Sciences, 2025)

Spatio-temporal variations in the diversity and occurrence of lutjanid fish species (Family: Lutjanidae) of the Gulf of Mannar, Southeast coast of India - M. Sharumathi; N. Jayakumar; R. Durairaja; J. Joyson Paul; C. Sudhan; M. Kalaiarasan; L. Ranjith (Marine Biodiversity, 2025)

Length-Weight Relationships and Condition Factor of 15 Coastal Fish Species (Family: Lethrinidae) of the Gulf of Mannar, Southeast Coast of India - Sanjay Chandravanshi; N. Jayakumar; R. Durairaja; S. Aanand; E. Suresh; C. Sudhan; M. Kishore Kumar; Mahesh Chand Sonwal; Adyasha Sahu (Thalassas: An International Journal of Marine Sciences, 2025)

Gingival Mesenchymal Stem Cells: A Periodontal Regenerative Substitute - Sonia S. Shetty; S. Sowmya; Aathira Pradeep; R. Jayakumar (Tissue Engineering and Regenerative Medicine, 2025)

A review of the physiological effects of microgravity and innovative formulation for space travelers - Jey Kumar Pachiyappan; Manali Patel; Parikshit Roychowdhury; Imrankhan Nizam; Raagul Seenivasan; Swathi Sudhakar; M. R. Jeyaprakash; Veera Venkata Satyanarayana Reddy Karri; Jayakumar Venkatesan; Priti Mehta; Sudhakar kothandan; Indhumathi Thirugnanasambandham; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

On the selection of humidification dehumidification desalination system cycle for high productivity, low energy consumption and low capital cost - P. Ranjitha Raj; J.S. Jayakumar; R. Ajith Kumar (Desalination, 2024)

Thirty-two years of smut disease status in the world’s largest sugarcane germplasm - R. Gopi; K. Chandran; A. Ramesh Sundar; R. Viswanathan; V. Jayakumar; Nisha M; B. Mahendran; Sony Jayaraman; Gireesan PP (Indian Phytopathology, 2024)

Overcoming multidrug resistance by reversan and exterminating glioblastoma and glioblastoma stem cells by delivering drug-loaded nanostructure hybrid lipid capsules (nHLCs) - Uzma Hasan; Meenakshi Chauhan; Suparna Mercy Basu; Jayakumar R.; Jyotsnendu Giri (Drug Delivery and Translational Research, 2024)

Editorial: Recent developments in oxygen minimum zones biogeochemistry - Annie Bourbonnais; Sudheesh Valliyodan; Mark A. Altabet; Amal Jayakumar; Syed Wajih Ahmad Naqvi; Gireesh Kumar T. R. (Frontiers in Marine Science, 2023)

A study on the occurrence of Burkholderia cepacia complex in ultrasound gels used in different veterinary clinical settings in India - Ravichandran Karthikeyan; Himani Agri; Akanksha Yadav; Varsha Jayakumar; Bhimavarapu Kiranmayee; Mathesh Karikalan; Mudit Chandra; Vanita Lyngdoh; Sandeep Ghatak; Dharmendra K Sinha; Bhoj R Singh (Veterinary Research Communications, 2023)

Comparative assessment of growth performance of indigenous and cross-bred calves subjected to combined stressors (heat and nutritional) - C. G. Shashank; R. G. Prashant; Parveen Kumar; Nitish A. Kulkarni; Manish Tiwari; S. Jayakumar; V. Sejian (International Journal of Biometeorology, 2023)

Toxicological effect of endocrine disrupting insecticide (deltamethrin) on enzymatical, haematological and histopathological changes in the freshwater iridescent shark, Pangasius hypothalamus - C. Prabhanjan Kumar Reddy; D. Manikandavelu; Ulaganathan Arisekar; B. Ahilan; A. Uma; N. Jayakumar; Woong Kim; Muthusamy Govarthanan; C. Harini; R. Sri Vidya; N. Madhavan; D. Ravindra Kumar Reddy (Environmental Toxicology and Pharmacology, 2023)

Estimation of Size Variation and Other Biometrics in Silver Pompano Trachinotus blochii(Lacepede, 1801) Reared in Different Farming conditions - Suresh Babu P. P; Anikuttan K. K; Anuraj A; Jayakumar R; Abdul Nazar A. K; Sakthivel M; Jayasree Loka; Imelda Joseph (Thalassas: An International Journal of Marine Sciences, 2023)

Monitoring of Harmful Algal Bloom (HAB) of Noctiluca scintillans (Macartney) along the Gulf of Mannar, India using in-situ and satellite observations and its impact on wild and maricultured finfishes - Rameshkumar. P; P.S. Thirumalaiselvan; Mini Raman; L. Remya; R. Jayakumar; M. Sakthivel; G. Tamilmani; M. Sankar; K.K. Anikuttan; N. Nandini Menon; Raju Saravanan; T.T. Ravikumar; et al. (Marine Pollution Bulletin, 2023)

Current and prognostic overview on the strategic exploitation of anaerobic digestion and digestate: A review - S. Chozhavendhan; G. Karthigadevi; B. Bharathiraja; R. Praveen Kumar; Lata Deso Abo; S. Venkatesa Prabhu; Ramalingam Balachandar; Mani Jayakumar (Environmental Research, 2023)

Invasion and distribution of exotic plants in the tropical forests of Western Ghats, India - R. Jayakumar; K. K. N. Nair (Tropical Ecology, 2022)

Impact of duration of stunting on compensatory growth and biometrics of snubnose pompano, Trachinotus blochii (Lacepede,1801) in low saline conditions - P. P. Suresh Babu; A. Anuraj; J. Loka; N. D. Praveen; K. Srinivasa Rao; M. T. Shilta; K. K. Anikuttan; R. Jayakumar; A. K. Abdul Nazar; I. Boby; J. Imelda (Thalassas: An International Journal of Marine Sciences, 2022)

Long-Term Sequelae of COVID-19 in Experimental Mice - Michael J. Paidas; Daniela S. Cosio; Saad Ali; Norma Sue Kenyon; Arumugam R. Jayakumar (Molecular Neurobiology, 2022)
We recently reported acute COVID-19 symptoms, clinical status, weight loss, multi-organ pathological changes, and animal death in a murine hepatitis virus-1 (MHV-1) coronavirus mouse model of COVID-19, which were similar to that observed in humans with COVID-19. We further examined long-term (12 months post-infection) sequelae of COVID-19 in these mice. Congested blood vessels, perivascular cavitation, pericellular halos, vacuolation of neuropils, pyknotic nuclei, acute eosinophilic necrosis, necrotic neurons with fragmented nuclei, and vacuolation were observed in the brain cortex 12 months post-MHV-1 infection. These changes were associated with increased reactive astrocytes and microglia, hyperphosphorylated TDP-43 and tau, and a decrease in synaptic protein synaptophysin-1, suggesting the possible long-term impact of SARS-CoV-2 infection on defective neuronal integrity. The lungs showed severe inflammation, bronchiolar airway wall thickening due to fibrotic remodeling, bronchioles with increased numbers of goblet cells in the epithelial lining, and bronchiole walls with increased numbers of inflammatory cells. Hearts showed severe interstitial edema, vascular congestion and dilation, nucleated red blood cells (RBCs), RBCs infiltrating between degenerative myocardial fibers, inflammatory cells and apoptotic bodies and acute myocyte necrosis, hypertrophy, and fibrosis. Long-term changes in the liver and kidney were less severe than those observed in the acute phase. Noteworthy, the treatment of infected mice with a small molecule synthetic peptide which prevents the binding of spike protein to its respective receptors significantly attenuated disease progression, as well as the pathological changes observed post-long-term infection. Collectively, these findings suggest that COVID-19 may result in long-term, irreversible changes predominantly in the brain, lung, and heart.

Mechanism underpinning the sharpening of orientation and spatial frequency selectivities in the tree shrew (Tupaia belangeri) primary visual cortex - Yamni S. Mohan; Sivaram Viswanathan; Jaikishan Jayakumar; Errol K. J. Lloyd; Trichur R. Vidyasagar (Brain Structure and Function, 2022)

Meso-scale foreshore evolution in low-energy, storm-dominated tropical west coast of India: Implications for shoreline management - Venkatraman S Hegde; Shailesh R Nayak; Girish K Huchchannavar; P A Krishnaprasad; A S Rajawat; G Shalini; S Jayakumar; Kanchanagouri D Gosavi; Lavanya G Hegde (Journal of Earth System Science, 2022)

Toward resolving disparate accounts of the extent and magnitude of nitrogen fixation in the Eastern Tropical South Pacific oxygen deficient zone - Corday R. Selden; Margaret R. Mulholland; Brittany Widner; Peter Bernhardt; Amal Jayakumar (Limnology and Oceanography, 2021)
Examination of dinitrogen (N 2 ) fixation in the Eastern Tropical South Pacific oxygen deficient zone has raised questions about the range of diazotrophs in the deep sea and their quantitative importance as a source of new nitrogen globally. However, technical considerations in the deployment of stable isotopes in quantifying N 2 fixation rates have complicated interpretation of this research. Here, we report the findings of a comprehensive survey of N 2 fixation within, above and below the Eastern Tropical South Pacific oxygen deficient zone. N 2 fixation rates were measured using a robust 15 N tracer method (bubble removal) that accounts for the slow dissolution of N 2 gas and calculated using a conservative approach. N 2 fixation was only detected in a subset of samples (8 of 125 replicated measurements) collected within suboxic waters ( μ mol O 2 kg −1 ) or at the oxycline. Most of these detectable rates were measured at nearshore stations, or where surface productivity was high. These findings support the hypothesis that low oxygen/high organic carbon conditions favor non‐cyanobacterial diazotrophs. Nevertheless, this study indicates that N 2 fixation is neither widespread nor quantitatively important throughout this region.

Biocontrol of Colletotrichum falcatum with volatile metabolites produced by endophytic bacteria and profiling VOCs by headspace SPME coupled with GC–MS - V. Jayakumar; A. Ramesh Sundar; R. Viswanathan (Sugar Tech, 2021)

Genome-wide discovery of SNPs in candidate genes related to production and fertility traits in Sahiwal cattle - M. R. Vineeth; T. Surya; Jayakumar Sivalingam; Anshuman Kumar; S. K. Niranjan; S. P. Dixit; Karanveer Singh; M. S. Tantia; I. D. Gupta (Tropical Animal Health and Production, 2020)

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Interaction of glyoxal with collagenous matrix and its behavioral aspects for non-toxic and sustainable tanning system - J. Kanagaraj; R. C. Panda; G. C. Jayakumar (International Journal of Environmental Science and Technology, 2020)

A WebGIS-Based Study for Managing Mangroves of Godavari Wetland, Andhra Pradesh, India - K. Jayakumar; V. Selvam; V. R. Prabavathy (Journal of the Indian Society of Remote Sensing, 2019)

Low rates of dinitrogen fixation in the eastern tropical South Pacific - Bonnie X. Chang; Amal Jayakumar; Brittany Widner; Peter Bernhardt; Calvin W. Mordy; Margaret R. Mulholland; Bess B. Ward (Limnology and Oceanography, 2019)
Recent work has suggested that the oxygen deficient zone (ODZ) and overlying surface waters of the eastern tropical South Pacific (ETSP) is a potential niche for dinitrogen (N 2 ) fixation. Rates of dinitrogen fixation were measured in the ETSP above and within the ODZ in July 2013 using a modified 15 N 2 bubble addition method, wherein a bubble was added, mixed, and then removed, and the isotopic enrichment of the dissolved N 2 was measured directly for each incubation. N 2 fixation rates in the euphotic zone ranged from below detection to 3.9 nmol L −1 d −1 and were below detection at all depths surveyed within the ODZ. Depth‐integrated rates ranged from below detection to 289.7 μ mol m −2 d −1 . DNA and RNA of diverse nifH genes were detected at both surface waters and in the ODZ. However, the results of this study suggest that N 2 fixation rates were low and contribute little to N cycling in the ETSP.

Biological Suppression of Sugarcane Smut with Endophytic Bacteria - V. Jayakumar; A. Ramesh Sundar; R. Viswanathan (Sugar Tech, 2019)

Correction to: Antimicrobial Drugs Encapsulated in Fibrin Nanoparticles for Treating Microbial Infested Wounds - B. Maria Alphonsa; P. T. Sudheesh Kumar; G. Praveen; Raja Biswas; K. P. Chennazhi; R. Jayakumar (Pharmaceutical Research, 2019)

Sub-physiological oxygen levels optimal for growth and survival of human atrial cardiac stem cells - Deepthi Sreerengam RajendranNair; Jayakumar Karunakaran; Renuka R. Nair (Molecular and Cellular Biochemistry, 2017)

Differential response of human cardiac stem cells and bone marrow mesenchymal stem cells to hypoxia–reoxygenation injury - Deepthi Sreerengam RajendranNair; Jayakumar Karunakaran; Renuka R. Nair (Molecular and Cellular Biochemistry, 2017)

Hydrochemical characteristics and quality assessment of groundwater in Amaravathi river basin of Karur district, Tamil Nadu, South India - A. Jafar Ahamed; K. Loganathan; R. Jayakumar (Sustainable Water Resources Management, 2015)

In Vitro and In Vivo Biological Evaluation of O-Carboxymethyl Chitosan Encapsulated Metformin Nanoparticles for Pancreatic Cancer Therapy - K. S. Snima; R. Jayakumar; Vinoth-Kumar Lakshmanan (Pharmaceutical Research, 2014)

Brain edema in acute liver failure: mechanisms and concepts - Kakulavarapu V. Rama Rao; Arumugam R. Jayakumar; Michael D. Norenberg (Metabolic Brain Disease, 2014)

The effect of organic carbon on fixed nitrogen loss in the eastern tropical South Pacific and Arabian Sea oxygen deficient zones - Bonnie X. Chang; Jeremy R. Rich; Amal Jayakumar; Hema Naik; Anil K. Pratihary; Richard G. Keil; Bess B. Ward; Allan H. Devol (Limnology and Oceanography, 2014)
The three major oxygen deficient zones (ODZs) of the world oceans (eastern tropical North and South Pacific (ETNP and ETSP, respectively), and Arabian Sea (AS) host the vast majority of pelagic fixed nitrogen (N) loss and up to half of total marine N loss. The input of organic matter is an important control on the absolute and relative importance of the two main pathways of N removal (denitrification and anammox). We investigated the response of N loss in the ETSP and AS ODZs to additions of organic matter in the form of glucose and naturally derived dissolved and particulate organic matter (DOM and POM, respectively). In the ETSP ODZ, the addition of glucose stimulated denitrification (1.6‐fold increase after 5 d) but not anammox (14‐fold decrease after 5 d). In the AS ODZ, only POM, not DOM, significantly increased rates of denitrification at the base of the oxycline (5.4–6.4‐fold increase after 2 d), but not at the secondary nitrite maximum. These results suggest that denitrification was generally limited by organic matter supply at the time of this study in both the ETSP and AS ODZs, although the lability of the organic matter supplied was important. Interestingly, 15 N 2 produced in ETSP and AS incubations was not binomially distributed relative to the reactants after the influence of anammox was taken into account, suggesting an unknown production mechanism or pathway of N removal.

Antimicrobial Drugs Encapsulated in Fibrin Nanoparticles for Treating Microbial Infested Wounds - B. Maria Alphonsa; P. T. Sudheesh Kumar; G. Praveen; Raja Biswas; K. P. Chennazhi; R. Jayakumar (Pharmaceutical Research, 2014)

Sulfonylurea Receptor 1 Contributes to the Astrocyte Swelling and Brain Edema in Acute Liver Failure - A. R. Jayakumar; V. Valdes; X. Y. Tong; N. Shamaladevi; W. Gonzalez; M. D. Norenberg (Translational Stroke Research, 2014)

Information processing bottlenecks in macaque posterior parietal cortex: an attentional blink? - Ryan T. Maloney; Jaikishan Jayakumar; Ekaterina V. Levichkina; Ivan N. Pigarev; Trichur R. Vidyasagar (Experimental Brain Research, 2013)

Endothelial-astrocytic interactions in acute liver failure - A. R. Jayakumar; M. D. Norenberg (Metabolic Brain Disease, 2013)

Distinctive effects of nano-sized permethrin in the environment - R. S. Suresh Kumar; P. J. Shiny; C. H. Anjali; Jayakumar Jerobin; Katrin Margulis Goshen; Shlomo Magdassi; Amitava Mukherjee; N. Chandrasekaran (Environmental Science and Pollution Research, 2013)

Metal Contamination in Select Species of Birds in Nilgiris District, Tamil Nadu, India - R. Jayakumar; S. Muralidharan (Bulletin of Environmental Contamination and Toxicology, 2011)

Lipid-Induced Conformational Transition of Amyloid β Peptide Fragments - Nagarajan Sureshbabu; R. Kirubagaran; H. Thangarajah; E. J. Padma Malar; R. Jayakumar (Journal of Molecular Neuroscience, 2010)

The Na–K–Cl Co-transporter in astrocyte swelling - Arumugam R. Jayakumar; Michael D. Norenberg (Metabolic Brain Disease, 2010)

Cytotoxic and anticarcinogenic activity of the ent-kaurene diterpenoid, melissoidesin, from Isodon wightii (Bentham) H. Hara - R. Thirugnanasampandan; R. Jayakumar (Natural Product Research, 2009)

Surfactant-induced conformational transition of amyloid β-peptide - N. Sureshbabu; R. Kirubagaran; R. Jayakumar (European Biophysics Journal, 2009)

Signaling factors in the mechanism of ammonia neurotoxicity - M. D. Norenberg; K. V. Rama Rao; A. R. Jayakumar (Metabolic Brain Disease, 2009)

Persistent Organochlorine Pesticide Residues in Tissues and Eggs of White-Backed Vulture, Gyps bengalensis from Different Locations in India - S. Muralidharan; V. Dhananjayan; Robert Risebrough; V. Prakash; R. Jayakumar; Peter H. Bloom (Bulletin of Environmental Contamination and Toxicology, 2008)

Efficacy of DL-α lipoic acid against systemic inflammation-induced mice: antioxidant defense system - E. Philip Jesudason; J. Gunasingh Masilamoni; Charles E. Jebaraj; Solomon F. D. Paul; R. Jayakumar (Molecular and Cellular Biochemistry, 2008)

Antiacetylcholinesterase and antioxidant ent -Kaurene diterpenoid, melissoidesin from Isodon wightii (Bentham) H. Hara - R. Thirugnanasampandan; R. Jayakumar; V. Narmatha Bai; Ebenezar Martin; K.J. Rajendra Prasad (Natural Product Research, 2008)

Inhibitory effects of short-term administration of dl-α-lipoic acid on oxidative vulnerability induced by Aβ amyloid fibrils (25–35) in mice - E. Philip Jesudason; J. Gunasingh Masilamoni; Ben S. Ashok; B’joe Baben; V. Arul; K. Samuel Jesudoss; W. Charles E. Jebaraj; S. Dhandayuthapani; S. Vignesh; R. Jayakumar (Molecular and Cellular Biochemistry, 2008)

New concepts in the mechanism of ammonia-induced astrocyte swelling - M. D. Norenberg; A. R. Jayakumar; K. V. Rama Rao; K. S. Panickar (Metabolic Brain Disease, 2007)

Influence of the macrotidal environment on the source to sink pathways of suspended flux in the Gulf of Kachchh, India: evidence from the Ocean Colour Monitor (IRS‐P4) - O. S. Chauhan; A. A. A. Menezes; S. Jayakumar; M. A. Malik; Y. Pradhan; A. S. Rajawat; S. R. Nayak; G. Bandekar; C. Almeida; M. Talaulikar; M. V. Ramanamurty; B. R. Subramanian (International Journal of Remote Sensing, 2007)

Detection of Rabies Virus Genes by In-Situ Polymerase Chain Reaction - P. Ezhil Praveena; R. Jayakumar; C. Balachandran; G. Thirumurugan; G. Dhinakar Raj; B. Murali Manohar (Veterinary Research Communications, 2007)

Anti-inflammatory effect of melatonin on Aβ vaccination in mice - E. Philip Jesudason; B’Joe Baben; Ben S. Ashok; J. Gunasingh Masilamoni; R. Kirubagaran; W. Charles E. Jebaraj; R. Jayakumar (Molecular and Cellular Biochemistry, 2007)

Rapid assessment on the impact of tsunami on mangrove vegetation of The Great Nicobar Island - R. Sridhar; T. Thangaradjou; L. Kannan; A. Ramachandran; S. Jayakumar (Journal of the Indian Society of Remote Sensing, 2006)

Mechanisms of Ammonia-Induced Astrocyte Swelling - M. D. Norenberg; K. V. Rama Rao; A. R. Jayakumar (Metabolic Brain Disease, 2005)

Altered structure and expression of RB1 gene and increased phosphorylation of pRb in human vestibular schwannomas - R. Thomas; P. D. Antony Herold Prabhu; J. Mathivanan; Rohini; D. Sivakumar; P. N. Jayakumar; B. Indira Devi; S. Satish; K. V. R. Sastry; R. Gope (Molecular and Cellular Biochemistry, 2005)

The protective role of DL-?-lipoic acid in the oxidative vulnerability triggered by A?-amyloid vaccination in mice - E. Philip Jesudason; J. Gunasingh Masilamoni; K. Samuel Jesudoss; R. Jayakumar (Molecular and Cellular Biochemistry, 2005)

Oxidative Stress in the Pathogenesis of Hepatic Encephalopathy - M. D. Norenberg; A. R. Jayakumar; K. V. Rama Rao (Metabolic Brain Disease, 2004)

Heavy Metals in Feathers of Six Species of Birds in the District Nilgiris, India - S. Muralidharan; R. Jayakumar; G. Vishnu (Bulletin of Environmental Contamination and Toxicology, 2004)

Ammonia Neurotoxicity: Role of the Mitochondrial Permeability Transition - K. V. Rama Rao; A. R. Jayakumar; M. D. Norenberg (Metabolic Brain Disease, 2003)

Muscle degeneration associated with cotton shrimp disease of Penaeus indicus - P. Ramasamy; R. Jayakumar; G P. Brennan (Journal of Fish Diseases, 2000)
Microsporidian disease of prawns has generally been recognized by the progressive white opacity associated with the musculature. Such microsporidian‐infected prawns are known as ‘cotton shrimp’, ‘milky white’ or ‘chalky white’ prawns. Microsporidians have been reported from prawns of several genera, notably Penaeus , Pandalus and Crangon ( Sprague & Couch 1971 ; Newman, Johnson & Pauley 1976 ). These diseases are highly pathogenic and cause epizootics in feral crustacean populations ( Iverson & Manning 1959 ; Overstreet 1973 ; Lightner, Fontaine & Hanks 1975 ; Sindermann 1990 ).

Latex immunoassay for rapid detection of newcastle disease virus - G. Thirumurugan; R. Jayakumar; K. Kumanan; A. T. Venugopalan; K. Nachimuthu (Tropical Animal Health and Production, 1997)